The determinants of health care expenditure: Testing pooling restrictions in small samples - Helmut Herwartz; Bernd Theilen (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
Healthcare expenditure has increased substantially in all western industrialized countries in the last decades. The necessity to contain the increase in health care expenditure has motivated the Analysis of its determinants to explain differences across countries and health systems. However, recent studies have questioned the use of cross~section data arguing that health systems are too different to allow for such comparisons. In this paper we investigate whether this criticism is really justified. We analyze the variations of health care expenditure in OECD countries relative to income, population aging and technological change. Our analysis is based on pooled cross-section data and time series. Firstly, formulating an error correction model for individual countries we demonstrate that for almost all of the countries investigated the variables are cointegrated. Secondly, we use a bootstrap framework for inference and examine whether the influence of the explanatory variables is unique across countries. Applying recursive estimation procedures we find that there is evidence for a common influence in the period 1961 to 1979 while in the last two decades explanatory variables have different impacts on health care expenditure across countries. This indicates the divergence of health systems and the growing importance of country-specific effects in the explanation of differences in health care expenditure across countries.
urn:nbn:de:kobv:11-10048048
Keywords: I11; C22; C23; 330